2019
DOI: 10.3390/agriculture9020033
|View full text |Cite
|
Sign up to set email alerts
|

Screening Corn Hybrids for Soil Waterlogging Tolerance at an Early Growth Stage

Abstract: Identification of corn hybrids that can withstand wet soil conditions is one approach to prevent crop production losses from abiotic stress caused by excessive soil moisture during early spring season in the midwestern United States. A greenhouse pot experiment was conducted in 2013 to screen and identify corn hybrids tolerant or susceptible to soil waterlogging at the V2 growth stage. The main plots included waterlogging durations: no waterlogging; 14-day waterlogging and then allowing recovery from waterlogg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 32 publications
(50 reference statements)
2
18
0
Order By: Relevance
“…Bragina et al [ 35 ] reported that plant height declined 7, 11, and 23% when corn was flooded for 1, 2, and 3 days, respectively, at the V2 stage. Other studies have also reported a reduced plant height due to waterlogging in the field [ 3 , 6 ].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Bragina et al [ 35 ] reported that plant height declined 7, 11, and 23% when corn was flooded for 1, 2, and 3 days, respectively, at the V2 stage. Other studies have also reported a reduced plant height due to waterlogging in the field [ 3 , 6 ].…”
Section: Resultsmentioning
confidence: 98%
“…Poor soil structure caused by natural or human influences may also restrict the internal drainage within the soil and further worsen waterlogging [ 5 ]. As the soil remains waterlogged, the soil redox potential declines [ 6 ], and the accumulation of reduced substances can reach phytotoxic levels [ 7 ]. Additionally, soil pH has been reported to increase due to protons’ consumption by reducing Fe and Mn oxides [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is envisaged that at the beginning of waterlogging stress, plant roots rapidly transmit a xylem-borne signals to the leaves in the form of hormones, most notably abscisic acid (ABA) to slow down the process of transpiration through stomatal closure, and thus attenuating carbon dioxide availability in leaves (Jackson et al, 2003;Najeeb et al, 2015). Coupled with decreased transpiration rate because of enhanced stomatal closure, the waterlogged-mediated anaerobic respiration triggered a drop in root hydraulic conductivity and an upsurge in root cell death, resulting in inadequate ATP for active delivery of water and nutrients to the shoots, thereby diminishing net photosynthetic rate (Steffens et al, 2005;Kaur et al, 2019). Henceforth, the supply of photoassimilates from leaves to different plant parts is also reduced, which ultimately leading to poor plant growth and biomass production (Kogawara et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…All pre-plant fertilizer N was uniformly surface broadcasted and then incorporated 15 cm deep immediately after application using a Tilloll (Landoll Corp., Marysville, KS, USA). Two commercially available corn hybrids, Hybrid #1 (P1360HR) and Hybrid #2 (P1498AM) (DuPont Pioneer, Johnston, IA, USA), used in this study were selected based on a greenhouse screening trial on flooding tolerance of commercially available corn hybrids in order to obtain one hybrid that showed tolerance and another that was less tolerant to soil waterlogging [31]. Hybrid #2 appeared to be more tolerant to waterlogging based on waterlogging screening in greenhouse experiment.…”
Section: Field Experimentsmentioning
confidence: 99%